2020
DOI: 10.37496/rbz4920200011
|View full text |Cite
|
Sign up to set email alerts
|

Production, egg quality, and intestinal morphometry of laying hens fed marine microalga

Abstract: The objective of the present study was to evaluate production and egg quality as well as the intestinal morphometry of laying hens fed diets supplemented with marine microalga Dunaliella salina. Six hundred laying hens were allocated based on a completely randomized design into five treatments (0, 0.25, 0.50, 0.75, and 1% inclusion of D. salina biomass) with 12 replicates of 10 hens per treatment. The experiment was divided into three periods of four weeks each, totaling 84 days. During this period, the produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
(27 reference statements)
1
7
0
Order By: Relevance
“…In the current study, dietary D. salina supplementation did not affect FI at all phases. These findings are in line with Fernandes et al (2020) , who stated that there was no significant difference for FI. In addition, FI did not differ significantly in broiler chicks fed a diet supplemented with algae extracts ( Alvarenga et al, 2011 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the current study, dietary D. salina supplementation did not affect FI at all phases. These findings are in line with Fernandes et al (2020) , who stated that there was no significant difference for FI. In addition, FI did not differ significantly in broiler chicks fed a diet supplemented with algae extracts ( Alvarenga et al, 2011 ).…”
Section: Discussionsupporting
confidence: 91%
“… Abdelwahab et al (2020) indicated that the substitution of fish meal with a low level of D. salina (33.0%) produced similar findings as the control diet with respect to BWG and FCR. Fernandes et al (2020) reported that D. salina has favorable bioactive concentrations of constituents, which may be used in poultry feed. Types present in seaweed are a good source of essential amino acids, such as tryptophan, phenylalanine, arginine, minerals, carbohydrates, and being rich in vitamins and β -carotene ( Abouelezz, 2017 ; Abd El-Hack et al, 2019 ; Hajati et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seaweed species such as Sargassum spp, Gracilaria sp, and Spirulina platensis present a good source of minerals, carbohydrates, and essential amino acids, such as arginine, tryptophan, and phenylalanine, being rich in beta-carotene and vitamins (Marín et al, 2009;Abouelezz, 2017;Ekýzoðlu et al, 2020;Hajati et al, 2020; ) and these algae and others of the same genus, when used in bird feeding, promote growth and increase in intestinal ora (Fernandes et al, 2020;Hajati & Zaghari, 2020;Rajesh & Pravin, 2021), with positive results in posture, improving animal performance and feed and water consumption (Melo et al, 2008aand 2008b, Carlos et al, 2011.…”
Section: Introductionmentioning
confidence: 99%
“…According to Fernandes et al (2020), although microalgae have desirable levels of bioactive compounds that can be used in the nutrition of laying hens, the patterns of deposition and egg enrichment may not be proportional to the inclusion level or period of dietary supplementation. So, it is necessary to develop research that can fill these gaps.…”
Section: Introductionmentioning
confidence: 99%